2016
DOI: 10.12956/tjpd.2016.199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory, Sociocultural and Demographic Features of the Type 1 Diabetes Mellitus Patients

Abstract: ÖzETAmaç: Tip 1 Diyabetes Mellitus (T1DM) çocukluk çağı ve adölesan dönemde en sık rastlanılan kronik endokrin hastalıklardan biridir. Çalışmada Keçiören Eğitim ve Araştırma Hastanesi Çocuk Endokrinoloji Polikliniği'nde düzenli olarak izlenen T1DM hastaların klinik, laboratuvar, sosyokültürel ve demografik özelliklerinin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntemler:Çocuk Endokrinoloji Polikliniği'nde 2007-2013 yılları arasında Tip 1 DM tanısı ile düzenli izlenen T1DM tanılı 0-18 yaş arasındaki 92 hasta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A study in Turkey (Demir et al 2015) reported T1DM was observed in two separate age groups; most commonly in the 6-8 age group followed by the 11-12 age group. In another study by Aydin et al they reported the most common age groups for T1DM diagnosis were 10-14 years and 14-18 years (Aydin et al 2016). In our study 17 patients (42.5%) were in the 3-9 age group and 25 (57.5%) were in the 10-16 age group.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A study in Turkey (Demir et al 2015) reported T1DM was observed in two separate age groups; most commonly in the 6-8 age group followed by the 11-12 age group. In another study by Aydin et al they reported the most common age groups for T1DM diagnosis were 10-14 years and 14-18 years (Aydin et al 2016). In our study 17 patients (42.5%) were in the 3-9 age group and 25 (57.5%) were in the 10-16 age group.…”
Section: Discussionsupporting
confidence: 55%
“…Another study in Germany reported the T1DM incidence in children under five was 6.86% in 1993 while it rose to 9.68% in 1995 (Rosenbauer et al 1999). Though the causes of this situation are not very clear, it is reported that environmental and nutritional factors may be responsible for these changes, not just genetic factors (Silink 2002;Aydin et al 2016). We consider the adoption of a sedentary lifestyle and increasing place of fast food style eating as the most important causes of the increase in T1DM incidence both in our country and globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous studies showed that the HbA1c values of young individuals with diabetes were high. This may have been caused by poor diabetes management . The present study found that there was a weak relationship between metabolic control and duration of life with diabetes.…”
Section: Discussionmentioning
confidence: 99%